UNVEILING THE POTENTIAL OF DIGITAL STORYTELLING IN NARRATIVE WRITING: A QUALITATIVE STUDY AT A VOCATIONAL HIGH SCHOOL - Maolida, Elis Homsini; Helmie, Jauhar; Setianingsih, Neng Ajeng Resma (Jurnal JOEPALLT (Journal of English Pedagogy, Linguistics, Literature, and Teaching), 2025)
Many students perceive writing, especially in English, as a complex and challenging task. Digital Storytelling (DS), which integrates audio, images, video, text, and interactive elements, has emerged as an innovative medium to support students in developing their narrative writing skills. This qualitative study explores the experiences and challenges faced by tenth-grade vocational high school students in West Java, Indonesia, when using DS as a medium for learning narrative writing. The findings reveal that students navigate five key stages: familiarizing themselves with the DS application, crafting their stories with teacher feedback, transferring content to DS, editing, and submitting their narratives. While digital storytelling fosters creativity, supports idea development, and provides students with a novel writing experience, it also presents challenges. These include difficulties in adding text, selecting suitable images, customizing text styles and colours, as well as technical issues related to devices and internet connectivity. The study highlights the importance of teacher preparation and proficiency with DS applications to ensure effective classroom implementation. These insights emphasize the potential of DS to transform narrative writing instruction while addressing its practical challenges.